2020
DOI: 10.1109/tmtt.2020.2999790
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Synthesis and Design of Ultralow Threshold 2:1 Parametric Frequency Dividers

Abstract: A new method is discussed for the systematic synthesis, design and performance optimization of varactor-based parametric frequency dividers (PFDs) exhibiting an ultra-low power threshold (P th ). For the first time, it is analytically shown that the P th -value exhibited by any PFD can always be expressed as an explicit closed-form function of the different impedances forming its network. Such a unique and unexplored property permits to rely on linear models, during the PFD design and performance optimization.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…1 d), where is the output power at delivered to the antenna used for transmission. , which designates the minimum input power at which a SubHT can operate, is set by the junction capacitance and tuning range exhibited by the adopted varactor, along with the impedances that such variable capacitor sees at both and 27 . These impedances are set by the equivalent passive network formed by the selected lumped components excluding the varactor.…”
Section: Principle Of Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…1 d), where is the output power at delivered to the antenna used for transmission. , which designates the minimum input power at which a SubHT can operate, is set by the junction capacitance and tuning range exhibited by the adopted varactor, along with the impedances that such variable capacitor sees at both and 27 . These impedances are set by the equivalent passive network formed by the selected lumped components excluding the varactor.…”
Section: Principle Of Operationmentioning
confidence: 99%
“…The thermistor was used as the required sensitive element in the SubHT stabilization network, allowing its unique temperature-sensitive dynamics. Following our recent theoretical investigation on the stability of varactor-based parametric systems 27 , and given the impedance exhibited at room temperature by the selected thermistor, the inductors and capacitors of the built SubHT were selected to minimize at equal to 886 MHz. This was done by satisfying four resonant conditions allowing the maximum voltage level across the varactor at , the minimum leakage of towards the receiving antenna and the lowest impedance magnitude seen by the varactor at .…”
Section: An Ultra-high-frequency (Uhf) Subht For Temperature Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermistor was used as the required sensitive element in the SubHT stabilization network, allowing its unique temperature-sensitive dynamics. Following our recent theoretical investigation on the stability of varactor-based parametric systems 27 , and given the impedance exhibited at room temperature by the selected thermistor, the inductors and capacitors of the built SubHT were selected to minimize P th at f in equal to 886MHz. This was done by satisfying four resonant conditions allowing the maximum voltage level across the varactor at f in , the minimum leakage of P out towards the receiving antenna and the lowest impedance magnitude seen by the varactor at f out .…”
Section: Varactor Thermistormentioning
confidence: 99%
“…Furthermore, while our preliminary measurements 53 already showed that the built SubHT enables longer communication 54 ranges, up to 7 meters, even longer ranges are expected in the future 55 through further technological and design developments. For instance, 56 as we theoretically discussed in27 , the minimum parametric power 57 threshold exhibited by any varactor-based parametric system is ul-58 timately set by the load and source characteristic impedances that, 59 for SubHTs, represent the input impedances of the adopted antennas. 60 Hence, through the future use of custom low-impedance (<10Ω) an-61 tenna designs, we anticipate to reduce this power threshold by more 62 than 200 times, thereby enabling much longer communication ranges 63 and higher sensitivities, which will be exclusively limited by the re-64 ceiver's power sensitivity and by the noise floor of the interrogating…”
mentioning
confidence: 99%